EFEKTIVITAS BERKUMUR EKSTRAK BUAH JERUK NIPIS (CITRUS AURANTIFOLIA) TERHADAP SKOR INDEKS PLAK GIGI (STUDI LITERATUR) (Jurnal Kesehatan Siliwangi, 2021)
Plaque is a soft deposit that forms a biofilm layer and adheres to the surface of the teeth, gums and oral tissue surfaces and is an indicator of dental and oral health. Chemical control of plaque can be done by using mouthwash which has antiseptic and antibacterial properties to inhibit bacterial growth and reduce the concentration of bacteria. In dental plaque. This study aims to analyze the effectiveness of gargling with lime fruit extract on dental plaque index scores. This type of research is a literature study. This type of research is a literature study. Methods of data collection by taking data in the library or official writings. The results of the literature review according to research on the effectiveness of lime extract solution as a mouthwash against plaque index in junior high school adolescents in Semarang and in kindergarten children with ECC (Early Childhood Caries) in Makassar there are significant differences in the plaque index before and before gargling lime extract, the higher concentration of lime extract, so the greater reduction in dental plaque index score.